2018
DOI: 10.1017/s1751731117002117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a photoperiodic green light programme during incubation on embryo development and hatch process

Abstract: This study was conducted to evaluate the effect of a 12-h light, 12-h dark (12L : 12D) photoperiod of green light during day 1 to day 18 of incubation time, on embryo growth, hormone concentration and the hatch process. In the test group, monochromatic light was provided by a total of 204 green light-emitting diodes (522 nm) mounted in a frame which was placed above the top tray of eggs to give even spread of illumination. No light-dark cycle was used in the control group. Four batches of eggs (n=300/group per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Factors such as temperature, humidity, turning and even carbon dioxide concentrations during incubation have been the most researched areas. These factors are extremely important, however, there is evidence that exposing embryos to light during incubation can have an effect on hatchability (Cooper, 1972;Shafey, 2004;Mench, 2014a and2014b;Archer, 2015a) and decrease incubation time (Ghatpande et al, 1995;Fairchild and Christensen, 2000;Tong et al, 2015). Light exposure has been seen to improve animal welfare posthatch as well (Archer et al, 2009;Özkan et al, 2012;Mench, 2014a and2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as temperature, humidity, turning and even carbon dioxide concentrations during incubation have been the most researched areas. These factors are extremely important, however, there is evidence that exposing embryos to light during incubation can have an effect on hatchability (Cooper, 1972;Shafey, 2004;Mench, 2014a and2014b;Archer, 2015a) and decrease incubation time (Ghatpande et al, 1995;Fairchild and Christensen, 2000;Tong et al, 2015). Light exposure has been seen to improve animal welfare posthatch as well (Archer et al, 2009;Özkan et al, 2012;Mench, 2014a and2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Overall,monochromatic green light stimulation shortened the hatching time. Similarly, Tong et al [9] reported a 3.4 h shortened hatching time in broilers under monochromatic green LED light stimulation. Decreased hatching time was earlier linked to increase in hatching weight, differences in thyroid hormone levels, organ weight and maturity, post-hatching growth, feeding and general behavior [24][25][26].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, providing monochromatic green light was shown to promote the growth of spleen [6] and skeletal muscle [7] in broilers. In addition, some studies have found a phenomenon that light stimulation during embryogenesis shortened the hatching time by using the light emitting diode lights (LED) [8,9]. The stimulating effect of monochromatic green light on skeletal muscle was linked to enhanced circulation levels of insulin-like growth factor 1 (IGF-1) in blood [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, monochromatic green light stimulation shortened the hatching time. Similarly, Tong et al [9] reported a 3.4 h shortened hatching time in broilers under monochromatic green LED light stimulation. Decreased hatching time was earlier linked to increase in hatching weight, differences in thyroid hormone levels, organ weight and maturity, post-hatching growth, feeding and general behavior [23,24].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, monochromatic green light was shown to promote the growth of spleen [6] and skeletal muscle [7] in broilers. Additionally, some studies have reported that light stimulation using light emitting diode (LED) during embryogenesis shortened the hatching time [8,9]. The stimulating effect of monochromatic green light on skeletal muscle was linked to enhanced circulation levels of insulin-like growth factor 1 (IGF-1) in blood [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%